A review of Neuropathic Pain: From Guidelines to Clinical Practice. Issue 1 (December 2017) - Cruccu, Giorgio; Truini, Andrea
Abstract Neuropathic pain is a chronic condition representing a significant burden for patients, society, and healthcare systems. The prevalence of neuropathic pain in the general population has been estimated at 7–8% and is expected to increase in the future. Neuropathic pain differs from nociceptive pain and requires a different therapeutic approach; and the management of neuropathic pain is complicated and challenging. This chapter discusses clinical practice guidelines for neuropathic pain and their usefulness in clinical practice. Funding: Pfizer, Italy.